2005
DOI: 10.1128/aem.71.3.1364-1372.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Doubly Phosphorylated Form of HPr, HPr(Ser-P)(His∼P), Is Abundant in Exponentially Growing Cells ofStreptococcus thermophilusand Phosphorylates the Lactose Transporter LacS as Efficiently as HPr(His∼P)

Abstract: In Streptococcus thermophilus, a lactic acid bacterium widely used by the dairy industry, lactose is transported via a secondary symporter-type transport system consisting of a single membrane protein, LacS, that belongs to the glycoside-pentoside-hexuronide:cation symporter family (34), a subgroup of the major facilitator superfamily (39). In most bacteria that use this mode of transport, internalized lactose is hydrolyzed by ␤-galactosidase into glucose and galactose, which are metabolized via the Embden-Mey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 57 publications
(73 reference statements)
2
28
0
1
Order By: Relevance
“…The ptsI gene located upstream from hprR ( Fig. 4) therefore remains the only presumed target for the 54 -dependent regulator in this organism.…”
Section: Proteins Containing a Pts Component Fused To The N Or C Termmentioning
confidence: 99%
See 2 more Smart Citations
“…The ptsI gene located upstream from hprR ( Fig. 4) therefore remains the only presumed target for the 54 -dependent regulator in this organism.…”
Section: Proteins Containing a Pts Component Fused To The N Or C Termmentioning
confidence: 99%
“…There are also numerous proteins of unknown function that contain a PTS domain (6). The PTS-mediated regulation of the lactose transporters from Streptococcus thermophilus (53) and Streptococcus salivarius (54) and of several transcription activators from firmicutes (1) and some Enterobacteriaceae, such as FrzR of E. coli (55), has been studied in detail.…”
Section: Proteins Containing a Pts Component Fused To The N Or C Termmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the role of the IIA domain of LacS had already shown that (i) the LacS-IIA domain is not essential for translocation (10); (ii) LacS is phosphorylated on His-552 by either HPr(His∼P) or HPr(Ser-P)(His∼P) (33,35,36), whereas LacS is not affected by HPr(Ser-P) (12); and (iii) the LacS-IIA domain modulates the activity of the carrier domain. However, it was not established whether regulation took place via interaction of the carrier domain with phosphorylated LacS-IIA, dephosphorylated LacS-IIA, or both LacS-IIA species.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of lactose counterflow upon phosphorylation of LacS-IIA by HPr(His∼P) is most likely caused by a direct interaction of the phosphorylated IIA domain with the carrier domain. As the levels of the different HPr species depend on the strain and growth phase of the organism (11,36), these parameters will determine which of the two histidinephosphorylated HPr species [HPr(His∼P) or HPr(Ser-P)-(His∼P)] will be most involved in the phosphorylation of LacS.…”
Section: Discussionmentioning
confidence: 99%